Obstetric care providers' knowledge, practice and associated factors towards active management of third stage of labor in Sidama Zone, South Ethiopia - Zelalem Tenaw; Zemenu Yohannes; Abdela Amano (BMC, 2017)
Abstract Background Active management of third stage of labor played a great role to prevent child birth related hemorrhage. However, maternal morbidity and mortality related to hemorrhage is high due to lack of knowledge and skill of obstetric care providers 'on active management of third stage of labor. Our study was aimed to assess knowledge, practice and associated factors of obstetric care providers (Midwives, Nurses and Health officers) on active management of third stage of labor in Sidama Zone, South Ethiopia. Methods An institution based cross sectional study design was conducted from December 1-30 /2015 among midwives, nurses and health officers. Simple random sampling technique was used to get the total of 528 participants. Data entry was done using EPI Info 3.5.1 and exported to SPSS version 20.0 software package for analysis. The presence of association between independent and dependent variables was assessed using odds ratio with 97% confidence interval by applying logistic regression model. Results Of the 528 obstetric care providers 37.7% and 32.8% were knowledgeable and skilled to manage third stage of labor respectively. After controlling for possible confounding factors, the result showed that pre/in service training, being midwife and graduation year were found to be the major predictors of proper active management of third stage of labor. Conclusion The knowledge and practice of obstetric care providers towards active management of third stage of labor can be improved with appropriate interventions like in-service trainings. This study also clearly showed that the level of knowledge and practice of obstetric care providers to wards active management of third stage of labor needs immediate attention of Universities and health science colleges better to revise their obstetrics course contents, health institutions and zonal health bureau should arrange trainings for their obstetrics care providers to enhance skill.